A 5.5-year observations of black carbon aerosol at a megacity in Central China: Levels, sources, and variation trends. (1st July 2020) - Zheng, Huang; Kong, Shaofei; Zheng, Mingming; Yan, Yingying; Yao, Liquan; Zheng, Shurui; Yan, Qin; Wu, Jian; Cheng, Yi; Chen, Nan; Bai, Yongqing; Zhao, Tianliang; et al.
Abstract: After releasing the Air Pollution Prevention Control and Action Plan (APPC) in China since 2013, the role of source emission control strategies and meteorological conditions on the reduction of air pollutants has received wide attention. Using an Aethalometer (AE31), equivalent black carbon (eBC) was monitored for 5.5-year after the APPC at Wuhan, a megacity in Central China, to identify its levels, sources, and variations trends. eBC varied in the range of 0.03–12.3 μg m −3, with the highest and lowest values in January (1.98 ± 1.70 μg m −3 ) and July (0.87 ± 0.61 μg m −3 ), respectively. The Kolmogorov-Zurbenk (KZ) filter and multiple-linear-regression were adopted to isolate the impacts of source emission control strategies and meteorological conditions on eBC variation. A long-term linear trend showed that emission-related reduction (7.79% yr −1 ) rather than meteorology-related reduction (4.51% yr −1 ) dominated the decreasing of eBC in the past years. Combining the KZ filter and Aethalometer model, the trends of eBC from fossil fuel combustion (eBC ff ) and biomass burning (eBC bb ) were calculated. eBC bb and eBC ff both showed decreasing trends with the reduction rates of 7.78% yr −1 and 7.76% yr −1, respectively. Backward trajectory analysis indicated that the air masses transported to the observational site from different regions in China all showed decreasing trend (1.64–18.7% yr −1 ) for eBC due to both the reduction from eBC bb (5.74–16.0% yr −1 ) and eBC ff (7.38–19.7% yr −1 ), suggesting the positive role of pollution control measures in migrating air pollution across China. Highlights: Human efforts dominate the reduction of black carbon. Biomass burning and fossil fuel both contribute to the reduction of black carbon. Black carbon reduction is joint efforts of local and regional prevention and control.